التحضر و أثره على الهوية لدى الشباب دراسة ميدانية على عينة من شباب مدينة الاغواط - بن علية اسماعيل; رداف لقمان (My University, 2023)
This study aimed to acknowledge the impact of urbanization on the social connections in the youth of 19-39 years old by exposing sign of change in the social life and their cultural identity caused by of technological development and modernity. The size of the study sample reached 647 young people of both sexes in order to highlight the nature of the urbanization impact on their connections and identity, thus, two partial hypotheses have been formulated to answer these questions: -The urbanization impacts the socio-cultural connections of youth in Laghouat city -The urbanization impacts the youth of Laghouat in new identities acquisition. In this study, we relied on the descriptive approach in which we used Questionnaire in collecting data. The study reached the following results: 1- The shorter the social connections between youth, the more it will be reflected in building friendships between them which negatively affected the psychological and social health of youth. 2- There is still prevalence in the values of solidarity and corporation among Laghouatian youth, an indication of their preservation of social values with the change in the forms of solidarity and corporation that were only limited to the field, that is to say, they help in the superficial matters and event of death as a part of solidarity especially in modern neighborhoods. 3- The city of Laghouat kept up with the requirements of urbanization linked to modern methods of communication that invaded youth and captured their desires. Such tools provided most youth with new and changing space to establish other relationships far from family present. Thus, it constitutes a threat to the future of familial relations. 4- We found that most of Laghouatian youth in their daily life communicate by mixing both Arabic and foreign languages added to Darija dialect. They are the people who have most access to network. 5- We found that most Laghouatian youth prefer modern clothes. They are the most used group of network as a result of the wave of urbanization, modernityand technological development, which led to the transformation of dressing style and fashion world entry. 6- We concluded that the youth acquired the imitation in dress culture through foreign cultural invasion and the mixing of cultures by imitating artist, athletes and celebrities and following them, which affected their sociocultural context and identity. Keywords: - Urbanization, Identity, Social Identity, Cultural Identity, New Identities, Youth